FOREIGN DIRECT INVESTMENTS IN WESTERN BALKANS: PRIVATIZATION, INSTITUTIONAL CHANGE AND BANKING SECTOR DOMINANCE - Botrić, Valerija (Economic Annals, 2010)
The paper provides analysis of foreign direct investment (FDI) dynamics and its determinants for the group of countries lately referred to as Western Balkans (non-EU ex-Yugoslavia countries plus Albania). Due to vulnerable external positions and enhanced funding requirements related to the EU accession and catching-up, FDI is often highly welcomed by government officials in the South East European (SEE) countries. The notion that FDI is frequently accompanied by knowledge and know-how transfer makes this source of capital growth even more desirable than simple capital accumulation from frequently inadequate domestic savings. The analysis of the FDI determinants on the overall economy level conducted within the panel data framework aims to provide the answer whether the same factors as in Central and Eastern European countries, now new EU member states, are relevant for the sampled countries. Due to data limitations and the frequent emergence of new countries in the region, the analysis does not extend to the early transition period. Since it entails the beginning of the financial crisis, the comparison of the results obtained with those of previous studies will enable the discussion of internal versus external factors of FDI attraction in the region.